Chromenopyrazole-based bipolar host materials for solution-processable thermally activated delayed fluorescence OLEDs exhibiting high efficiency and low roll-off. Issue 86 (11th October 2019) - Godumala, Mallesham; Yoon, Jiwon; Lee, Chiho; Jeong, Ji-Eun; Park, Sungnam; Woo, Han Young; Cho, Min Ju; Choi, Dong Hoon
Abstract : With chromenopyrazole as an electron-acceptor core, two new bipolar host materials (DCzCP and TCzCP ) exhibited high performance and low roll-off in solution-processable TADF-OLEDs. Abstract : This study reports the design, synthesis, and characterization of two new bipolar host materials, DCzCP and TCzCP . Both materials were implemented as hosts by doping a known green thermally activated delayed fluorescent (TADF) emitter (t4CzIPN ) in solution-processable OLEDs. DCzCP -based devices afford the best performance with the maximum external quantum efficiency (EQE) of 21.2%. Notably, the EQE was maintained at 20.7% and 19.7% at a practical luminance of 500 cd m −2 and 1000 cd m −2, respectively, demonstrating very small roll-off.